COMPARISON OF DIFFERENT AUTOMATED STRATEGIES FOR CALIBRATION OF RAINFALL-RUNOFF MODELS - Madsen H.; Wilson G.; Ammentorp H.C. (My University, 2002)
Three different automated methods for calibration of rainfall-runoff models are presented and compared. The methods represent various calibration strategies that utilise multiple objectives and allow user intervention on different levels and different stages in the calibration process. The methods have been applied for calibration of a test catchment and compared on validation data with respect to overall performance measures in terms of water balance error and general hydrograph shape, and simulation of high and low flow events. The results illustrate the problem of non-uniqueness in model calibration since none of the methods are superior with respect to all performance measures considered. In general, the different methods put emphasis on different response modes of the hydrograph. Calibration based on the use of generic search routines in combination with user-specified calibration priorities is seen to compare favourably with an expert system that is designed for the specific model being considered and requires user intervention during the entire calibration process.
Keywords: RAINFALL-RUNOFF MODELS; CALIBRATION; PARAMETER ESTIMATION; OPTIMISATION ROUTINE; EXPERT SYSTEM